2013
DOI: 10.1186/1471-2164-14-s2-s1
|View full text |Cite
|
Sign up to set email alerts
|

New enumeration algorithm for protein structure comparison and classification

Abstract: BackgroundProtein structure comparison and classification is an effective method for exploring protein structure-function relations. This problem is computationally challenging. Many different computational approaches for protein structure comparison apply the secondary structure elements (SSEs) representation of protein structures.ResultsWe study the complexity of the protein structure comparison problem based on a mixed-graph model with respect to different computational frameworks. We develop an effective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…A slight variation of p-OLSE was considered in [3,25], where the linear order imposed on G and H was replaced with a partial order (directed acyclic graphs); the problem was referred to as the Graph Embedding problem in [3] and as the Generalized Subgraph Isomorphism problem in [25]. The aforementioned problems were mainly studied in [3,25] assuming no bound on ∆ H and ∆ G and, not surprisingly, only hardness results were derived. In [25], a parameterized algorithm with respect to the treewidth of G and the map width ∆ L combined was given.…”
Section: Previous Related Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A slight variation of p-OLSE was considered in [3,25], where the linear order imposed on G and H was replaced with a partial order (directed acyclic graphs); the problem was referred to as the Graph Embedding problem in [3] and as the Generalized Subgraph Isomorphism problem in [25]. The aforementioned problems were mainly studied in [3,25] assuming no bound on ∆ H and ∆ G and, not surprisingly, only hardness results were derived. In [25], a parameterized algorithm with respect to the treewidth of G and the map width ∆ L combined was given.…”
Section: Previous Related Resultsmentioning
confidence: 99%
“…In [25], a parameterized algorithm with respect to the treewidth of G and the map width ∆ L combined was given. Most of the hardness results in [3,25] were obtained by a direct reduction from the Independent Set or Clique problems. For example, it was shown in [3] that the problem of embedding the whole graph G into H is N P-hard, but is in P if ∆ L = 2.…”
Section: Previous Related Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus protein structure comparison methods are indispensable. Article S1 by Xiuzhen Huang et al (Arkansas State University) describes ePC, an accurate and fast algorithm that is able to compare whole structures as well as specific substructures [38]. As detailed in article S4 [39], Prasad Gajula (Indian Agricultural Statistics Research Institute) presented a molecular dynamics simulation of the protein Vinculin and showed that the simulation is highly consistent with local mobility as determined experimentally by electron paramagnetic resonance (EPR) spectroscopy.…”
Section: Protein Structure and Functionmentioning
confidence: 99%
“…Several other methods have been proposed from shape-based descriptors (Røgen and Fain, 2003) to knot-fittinginspired methods (Erdmann, 2005) to qualify and quantify structural similarity. Automated protein structural classification methods have relied on machine learning (Jain and Hirst, 2010), clustering and graph theory based approaches (Ashby et al, 2013;Kim and Patel, 2006). Sequence based protein classification techniques have focused on identifying common motifs and domains and using these to cluster them together.…”
Section: Introductionmentioning
confidence: 99%